2015
DOI: 10.1097/bcr.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

The Reported Pain Coping Strategies of Pediatric Burn Survivors—Does a Correlation Exist Between Coping Style and Development of Anxiety Disorder?

Abstract: Unresolved pediatric pain, both acute and chronic, has been associated with negative short- and long-term physical and mental health outcomes. This study sought to determine whether an association existed between self-reported pain coping skills and anxiety levels in a cohort of pediatric burn patients, and whether gender would influence their responses. The sample comprised burn-injured children in attendance at one of three mature burn camp sites. The self-report measures utilized included the 41-item Screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A study by Rimmer et al found children engaging in internalization coping behaviors such as catastrophizing to be more likely to develop long-term anxiety disorders, indicating that adverse psychological outcomes in children may be directly mediated by patients' pain coping strategies. 16 While children with maladaptive pain coping strategies had an increased risk of developing anxiety disorders, patients using behavioral distraction did not. 16 This suggests distraction-based nonpharmacologic pain treatments may improve the risk of long-term psychological sequelae of burns in children.…”
Section: Long-term Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Rimmer et al found children engaging in internalization coping behaviors such as catastrophizing to be more likely to develop long-term anxiety disorders, indicating that adverse psychological outcomes in children may be directly mediated by patients' pain coping strategies. 16 While children with maladaptive pain coping strategies had an increased risk of developing anxiety disorders, patients using behavioral distraction did not. 16 This suggests distraction-based nonpharmacologic pain treatments may improve the risk of long-term psychological sequelae of burns in children.…”
Section: Long-term Implicationsmentioning
confidence: 99%
“…16 While children with maladaptive pain coping strategies had an increased risk of developing anxiety disorders, patients using behavioral distraction did not. 16 This suggests distraction-based nonpharmacologic pain treatments may improve the risk of long-term psychological sequelae of burns in children.…”
Section: Long-term Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A child or adolescent's choice of coping strategies can have beneficial or detrimental effects on their overall well-being. Adaptive coping strategies, such as information seeking, 4 , 39 may lessen negative physical and mental consequences of chronic pain in childhood 8 ; whereas avoidant coping, passive coping, or catastrophizing about the pain is associated with elevated psychological distress, 11 , 27 , 28 , 38 a more intense pain experience, 20 , 43 , 47 and increased functional disability. 10 , 21 , 31 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, active coping strategies (i.e., seeking social support, problem solving, and openly talking about stressors) are most effective for promoting the psychosocial adjustment of chronically ill pediatric patients ( Meijer et al, 2002 ) and a key to family functioning and support in pediatric oncology patients ( Trask et al, 2003 ; Martin et al, 2012 ). In the context of pediatric burns, adaptive coping strategies are negatively associated with post-traumatic stress symptoms ( Enlow et al, 2019 ), whereas internalizing (e.g., rumination, fixating on anxieties) and externalizing coping behaviors (e.g., screaming, breaking things) have been related to greater panic and general anxiety disorder symptoms ( Rimmer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%